(untitled) (Teacher’s World: Journal of Education and Research, 2023)
The fundamental target of the self-assessment is to assist institutions to in improving the quality of education and setting priorities in improvement plan as per requirements of relevant stakeholders and following the vision of a nation which requires a huge self-inspiration of faculty members’ within the organization. Universities in Bangladesh have already completed a self-assessment programme and this paper aims to investigate faculty members’ perception and perceived change impact of organizational self-assessment process on academic units using both qualitative and quantitative approaches. The SAC members’ perception on the self-assessment process is collected using likert scale. Overall, mean score implies that SA members are convinced with the standards set for SA process. Organizational improvement priorities and perceived change impacts are identified through Nvivo and in-depth interviews respectively. Although there are some priorities set by them cannot be executed without a grant, only a few departments are chipping away at their improvement plan. However, it is reported that, there is a big change happened in the affective domain of faculty members. Teacher’s World: Journal of Education and Research, Vol. 48(2), Dec 2022, p.67-82